A eficácia dos direitos fundamentais na ordem jurídica privada - Liliana Lopes Nery (2012)
It is through the Constitution of a nation, that the rights of the components of a society are recognized. The declaration of fundamental rights is the core of a democratic constitution, once it is through effectiveness of fundamental subjective rights that the law rights make freedom and other values possible. The relation between fundamentalrights and private rights can become controversial at times, when they can both merge in various premises and to a certain extend they might be irreconcilable. We just have to think in the private autonomy from one side and fundamental rights inalienability, absence of waive and imprescriptibility on the other. The human freedom can be threaten not only by the State, but also by private institutions (which have economicand social power), the reason why the fundamental rights should be taken as a whole, valid on the face of the legal system and opposite in the citizen/State relationships, as well as in the relations among private ones. The preciput objective of this research is to identify the effects that norms of fundamental rights produce in the relations among private ones how and to what extent, as well as number diverging models (patterns)and their main criticisms. Different aspects of the law will be confronted and compared; furthermore analyses of the STF jurisprudence will also be done. After most, as indissociable, it will emerge in the general theory of fundamental rights in order to provide a deeper and more specific study of those, moreover in what is tangible in its applicability, efficiency and extension.